Análise de expressão de isoformas pró-angiogênica e anti-angiogênica do gene VEGF e controle de Splicing em câncer de mama - Castro, Rodrigo (2013)
Introduction : The growth and progression of tumors depend on angiogenesis , the process of formation of new blood vessels from a pre-existing endothelium . The vascular endothelial growth factor (VEGF or VEGF - A) is a potent mitogen for endothelial cells and increased expression is associated with tumor growth and metastasis . However, the selection of alternative splicing site in the 3 'end of exon 8 of the VEGF gene results in a sister family of isoforms , VEGF- Axxxb , which are anti- angiogenic and downregulated in tumor tissues . Objectives : To assess quantitatively the expression of isoforms pro- angiogenic and anti- angiogenic VEGF gene into 50 samples of breast cancer and normal adjacent tissue and determining the effect of regulatory proteins to control the event splicing of the VEGF gene regulatory proteins and Splicing , SRPK1 , SRp40 , SRp55 and ASF/SF2 . Methods: The expression of VEGF Axxx, VEGF-A165b isoforms and Splicing regulatory proteins were analyzed by PCR quantitative real-time (PCRq ) using samples from 50 patients with breast cancer and 43 adjacent normal tissue used as controls . Values of Relative Quantification (RQ) were used in association with molecular subtypes and metastasis. The data were tested for normality D' Agostino and Pearson normality test using the program GraphPadPrismv.6 . The values of relative mRNA quantification ( RQ ) of the VEGF-A isoforms and splice regulatory proteins in tumors was analyzed by Wilcoxon Signed Rank Test , since the data is not normal distribution . Spearman correlation was used to evaluate the correlation between the levels of mRNA expression between regulatory proteins and VEGF-Axxx and VEGF-A165b isoforms where P values ≤ 0.05 were considered significant. Results: Expression significantly increased both isoforms of VEGF- Axxx (median RQ = 7.7, P <0.0001) and VEGF- A165b (median RQ = 2.9 , P < 0.0001) was seen in breast tumors compared to adjacent normal tissues . Comparing the values of expression of VEGF- A165b and VEGF - Axxx by the Mann -Whitney test that showed no significant difference in expression of isoforms in tumors ( P = 0.065 ) . The mRNA expression of SRPK1 protein was significantly elevated in breast tumors compared to normal tissue (P < 0.0001). For ASF/SF2, SRp55 and SRp40 mRNA expression also showed significantly elevated in the tumors (P < 0.0001). Proteins ASF/SF2 , SRp55 , SRp40 and SRPK1 showed positive correlation with both isoforms of VEGF -A . We also found a positive correlation SRPK1 protein with all other SR proteins , mainly ASF/SF2. Conclusion: The concept of alternative splicing of the VEGF-A gene results in isoforms anti- angiogenic and pro- angiogenic research indicates that the quantitative changes in VEGF-A molecule in cancer and other diseases may be insufficient . As shown, the expression of splicing regulatory protein studied here were all positive as compared to the VEGF-A165b and VEGF- Axxx isoforms .